Synthetic and therapeutic review of triazoles and hybrids - Goyal Akshi; Bhandari Meena (Heterocyclic Communications, 2024)
Triazoles act as important pharmacophores in showing biological activity such as antibacterial, antifungal, antitumour/anticancer, anti-inflammatory activities. Literature review suggests that triazoles have been maximally used in carrying research related activities in reference to biological evaluation as compared to other nitrogen containing five membered heterocycles like tetrazoles, pentazoles, pyrazoles, and imidazoles. The first compound of this class was discovered by Janseen Group in 1960s. The microbes act counteractively towards antibiotics which in turn challenge the efficacy of the drugs and thus create room for the progression of more potent avant-garde drugs. Thus, the synthesis of hybrid molecules has been accelerated from last two decades as the hybrids possess more potency, vigour, and adequacy than its constituting pharmacophores. So, this review represents a condensed report of the research carried out in relation to synthetical procedures and assessment of the antibacterial and antifungal activity of triazoles.